The Advantages of Creative Industries Based on Local Wisdom in Enhancing Tourism Destination Image: Implications for Sustainable Tourism - Andriani, Nurita; Miftahul Jannah, (Proceeding of International Management Conference and Progressive Papers, 2024)
This local wisdom is a destination that differentiates one tourism area from another. Tourism based on local wisdom is now a tourism promotion commodity sold to the public as a tourist attraction. Local wisdom teaches moral values, ethics, and increases the love for local cultures. This study aims to analyze the advantages of local wisdom-based creative industries in improving the image destinations, and its implications on tourist visiting decisions to realize sustainable tourism in Sumenep Regency.This study uses an approach in the form of a quantitative research method. The location of the study is a tourist destination in Sumenep Regency, namely Slopeng Beach, Lombang Beach, and Keraton Tourism. The sample of this study was visitors to the tourist destinations of Slopeng Beach, Lombang Beach, and Keraton Tourism in Sumenep Regency, while the sampling technique used purposive samplingwith the criteria, having visited one of the specified tourist destinations and having visited at least twice and visiting in the last 1 year. The analysis method used is using PLS-SEM analysis with the SmartPLS device. The results of this study found that the advantages of local-based creative industries influences the image destinations, the the advantages of local-based creative industries influences on tourist visiting decisions, the image destinations influences tourist visiting decisions and the advantages of local-based creative industries influences tourist visiting decisions mediated by the image destinations, and its implications towards sustainable tourism in Sumenep Regency.